THE DECONSTRUCTION OF THE MASS CULTURAL INDUSTRIAL POWER RELATION OF THE WOODEN STATUE ARTISANS AT KEMENUH VILLAGE, SUKAWATI, BALI - Mardika, I Made (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2017)
It is important to deconstruct the development of the mass wooden statue industry at Kemenuh, Sukawati District, Gianyar, Bali. The reason is that the artisans are presumed to have been marginalized by capital strength. This present study is intended to answer the ideology which has inspired the mass wooden statue industry, the power practice performed by the agencies, and its implication on the life of the artisans. The study used the approach of cultural studies and the critical social theories. The data were analyzed qualitatively. The result of the study shows that, first, the ideology which has inspired the artisans to develop the mass wooden statue industry is the ‘great’ capitalistic ideology which is mixed with the Balinese ideology, causing the synthetic and pluralistic ideology to be formed. Second, the hierarchical and symmetrical power practice performed by the agencies. The capital owners, distributors and consumers dominate and exploit the artisans. Third, the mass cultural industry has economically, socially and culturally affected the life of the artisans. However, their economy has been better but they are getting marginalized; their gender equality is getting stronger but their traditional social structure is getting instable; and their art creativity has improved but the connotation of their mass culture is getting lower.